An enhanced tree-based key management scheme for secure communication in wireless sensor network - Rasul, Khadija; Nuerie, Nujhat; Pathan, Al-Sakib Khan (2010)
In this paper, we present an enhanced heterogeneous tree based key management scheme for security of Wireless Sensor Networks (WSNs). Our scheme combines efficiently different key management techniques in each architecture level and also it has a dynamic key renewal process. Here, whenever a node is compromised, key renewal is done by one way hash functions and simple XOR operations. This combination gives the scheme good performance in terms of key storage overhead as well as resilience to the node capture attack. We compare our scheme with other heterogeneous schemes and show that our scheme gives better performance.